Landscape complexity and edge effects shape bird community composition and filter functional traits in villages - Tamás Lakatos; András Báldi; Zoltán Benkő; Róbert Gallé; Dávid Korányi; István Kovács; Zoltán László; Jenő J. Purger; Krisztina Sándor; Gábor Seress; István Urák; Péter Batáry (Ecological Indicators)
As agricultural intensification and urban sprawl threaten global ecosystems, preserving high-biodiversity habitats, even within settlements, is paramount. Many European villages still retain a traditional structure, which can support biodiversity. However, the surrounding landscape and within-village position could determine bird species composition and functional traits. We examined how bird functional traits (diet, nest location, body mass, nestling diet, foraging technique, migration status), species composition, and predation on dummy caterpillars were affected by landscape-scale variables in 64 villages in Hungary and Romania. Specifically, we studied the effects of landscape complexity around the villages (simple, agriculture-dominated vs. complex, forested-dominated), village proximity to cities (in agglomeration vs. far from cities), and sampling position within villages (centre vs. edge). Our results showed that landscape complexity and within-village position were key determinants of bird functional trait variation. We observed a shift towards carnivorous (also in the case of nestling diet) and more ground nesters at village edges and in complex landscapes. In contrast, larger-bodied bird species preferred villages in simple landscapes. Bird predation was higher in simple landscapes within city agglomerations but this pattern was the opposite far from cities, possibly due to varying food resource availability. These findings underscore the importance of enhancing landscape features in and around villages, particularly in simple landscapes and village centres.